2021
DOI: 10.4330/wjc.v13.i12.650
|View full text |Cite
|
Sign up to set email alerts
|

Improving the heart team: An interdisciplinary team and integrated practice unit

Abstract: Heart Team emerged as an important tool in the cardiovascular care, improving the efficiency of decision-making process. In addition to the benefits in patient care, it symbolizes a new culture and mindset. However, beyond the clinical condition, in low/middle-income countries other concerns arise regarding patient's background and these demands are, usually, as challenging as the medical treatment. New models have been proposed face these demands and to assure a holistic care by Integrated Practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“… 3 Alternatively, Tremblay et al 38 found that patients with cancer under the care of teams working with a greater interdisciplinary intensity reported four times greater access to care compared with lower intensity teams; access which our participants reported as a major difficulty. Furthermore, Veronese et al 39 found improvements in surgery waiting times through interdisciplinary teamwork even when factoring in socioeconomic barriers in upper-middle-income countries. Therefore, facilitating access through a ‘buffet-style’ approach in an interdisciplinary manner should ensure greater access to, and equity of, care.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Alternatively, Tremblay et al 38 found that patients with cancer under the care of teams working with a greater interdisciplinary intensity reported four times greater access to care compared with lower intensity teams; access which our participants reported as a major difficulty. Furthermore, Veronese et al 39 found improvements in surgery waiting times through interdisciplinary teamwork even when factoring in socioeconomic barriers in upper-middle-income countries. Therefore, facilitating access through a ‘buffet-style’ approach in an interdisciplinary manner should ensure greater access to, and equity of, care.…”
Section: Discussionmentioning
confidence: 99%
“…Even with increasing research into the nuances of different patient populations, there are limitations to applying trial-derived recommendations to real-world scenarios. Clinical trials abide by strict eligibility criteria that challenge the generalizability of their findings, with half to three-quarters of all real-world patients meeting clinical criteria that would make them ineligible for enrolment in contemporary trials [38,39] . This is one of many benefits of a Heart Team approach, as it interprets multidisciplinary evidence in the context of the patient's unique clinical profile to facilitate shared decision-making and personalized care [40] .…”
Section: Treatment Of Cad With Reduced Lvefmentioning
confidence: 99%